An analytical model for evaluating the grid impacts of wind power plants - Padilla, Gilba Joy R. (2004)
This research developed analytical models and methodology to evaluate the impacts of integrating intermittent wind power plants (WPPs) to an electric grid. The methodology uses the method of cumulants and Gram-Charlier series expansion to simplify the convolution calculations in probabilistic load flow and steady-state stability simulations of the grid. The probability of outages of conventional generating units, weibull probability distributions of wind speed, and probability distributions of load were used in the simulations to consider the stochastic nature in power system operation. The usefulness of the models and methodology was demonstrated in an application study that determined the effects of WPPs to a 24-bus (Area A) IEEE Reliability Test System (1996).